Gillick competence: an inadequate guide to the ethics of involving adolescents in decision-making - Bart, Avraham (Journal of medical ethics, 2024)
Developmentally, adolescence sits in transition between childhood and adulthood. Involving adolescents in their medical decision-making prompts important and complex ethical questions. Originating in the UK, the concept of Gillick competence is a dominant framework for navigating adolescent medical decision-making from legal, ethical and clinical perspectives and is commonly treated as comprehensive. In this paper, we argue that its utility is far more limited, and hence over-reliance on Gillick risks undermining rather than promoting ethically appropriate adolescent involvement. We demonstrate that Gillick only provides guidance in the limited range of cases where legal decisional authority needs to be clarified. The range of cases where use of Gillick actually promotes adolescent involvement is narrower still, because several features must be present for Gillick to be enacted. Each of these features can, and do, act as barriers to adolescent involvement. Within these limited situations, we argue that Gillick is not specific or strong enough and is reliant on ethically contestable principles. Moreover, in most situations in adolescent healthcare, Gillick is silent on the ethical questions around involving adolescents. This is because it focuses on decisional authority—having the final say in decision-making—which is one small subset of the many ways adolescents could be involved in decision-making. The implication of our analysis is that use of Gillick competence tends to limit or undermine adolescent involvement opportunities. We propose that those working with adolescents should be judicious in seeking Gillick’s guidance, instead drawing on and developing alternative frameworks that provide a comprehensive model for adolescent involvement.